Coordination of Caregiver Naming and Children’s Exploration of Solid Objects and Nonsolid Substances - Perry, Lynn K.; Custode, Stephanie A.; Fasano, Regina M.; Gonzalez, Brittney M.; Valtierra, Adriana M. (Frontiers in Psychology, 2022)
When a caregiver names objects dominating a child’s view, the association between object and name is unambiguous and children are more likely to learn the object’s name. Children also learn to name things other than solid objects, including nonsolid substances like applesauce. However, it is unknown how caregivers structure linguistic and exploratory experiences with nonsolids to support learning. In this exploratory study of caregivers and children (n=14, 8 girls; M=20.50 months) we compare caregiver-child free-play with novel solid objects and novel nonsolid substances to identify the linguistic and exploratory experiences associated with children’s word learning. We found systematic differences in interactions with novel objects, such that children performed more manual actions on solids than nonsolids and caregivers named solids more than nonsolids. Additionally, there was less synchrony between caregivers’ naming and children’s manual and visual exploration of nonsolids than solids. Consistent with prior work, we found that synchronous naming was associated with accurate recognition of solid object names. However, naming synchrony was not associated with recognition of nonsolid substance names or with generalization. Together these findings, though exploratory, suggest the coordination of caregiver-child play can shape what children remember about novel word-object associations for solid objects, but not nonsolid substances.